Implementasi Metode Role Playing Pada Mata Pelajaran Fiqih Dan Implikasinya Terhadap Pemahaman Siswa Pada Materi Memandikan Jenazah (Studi di Kelas IX 1 MTsN 1 GARUT) - Sulaiman, Husnan; Dewi, Lyusni Anisa (STAI Al-Musaddadiyah Garut, 2023)
This study is motivated by the researcher’s concern regarding the continuity of the teaching and learning process, particularly in enhancing students' understanding in the subject of Fiqh, especially practical topics. Observations revealed that many ninth-grade students at MTsN 1 Garut struggle with comprehending the practical aspects of washing a deceased body. This necessitates the application of a practical teaching method. The objectives of this research are: (1) to describe the understanding of ninth-grade students regarding the practice of washing a deceased body at Madrasah Tsanawiyah Negeri 1 Garut; (2) to detail the implementation of the Role Playing method in teaching the practice of washing a deceased body to ninth-grade students at Madrasah Tsanawiyah Negeri 1 Garut; (3) to assess the impact of the Role Playing method on students’ understanding of the practice of washing a deceased body. The research employs a descriptive qualitative method aimed at illustrating or describing occurrences in the field. Additionally, it is supported by library research methods. The primary data sources include observations of the learning process and the practical sessions on washing a deceased body conducted at MTsN 1 Garut. Secondary sources consist of books or other reading materials directly related to the research. Data collection techniques involve observations, interviews, and documentation. The data analysis techniques employed are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of the Role Playing method in the Fiqh subject and its implications for students’ understanding have successfully met 4 out of 7 understanding indicators. These are the findings derived from this research. Keywords: Role Playing Teaching Method, Fiqh Subject, Students’ Understanding